Recreational activities to motivate the learning of children with Down síndrome/Actividades recreativas para motivar el aprendizaje de los niños con síndrome de Down - Ronald Humberto Véliz Ortega; Jorge Luis Mateo Sánchez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Recreational activities can enhance various variables for the teaching of various elements in children with Down syndrome, which can improve the subject's quality of life, through the scientific application of appropriate physical stimuli and adapted to the context. The objective of this research was to theoretically validate the importance of recreational activities to motivate the learning of children with Down syndrome from different analysis variables. The research is exploratory, with a descriptive-explanatory and correlational orientation, 31 specialists from two independent groups are consulted (Group 1: National Specialists: 16 subjects; Group 2: International Specialists: 15 subjects). The importance of recreational activities in basic (HFB in Spanish) and specific (HFE in Spanish) physical skills, the formation of values (FV in Spanish), cognitive skills (HC in Spanish) and ludic culture (CL in Spanish) is validated. The criteria issued by the independent groups did not show significant differences in the variables "HFB" (p=0.626), "FV" (p=0.545) and "CL" (p=0.861), but in the variables "HFE" ( p=0.000) and "HC" (p=0.000). The need for an update of knowledge in national specialists in the last two variables described is evident. Of the variables analyzed, "HFB" has a greater relative importance, followed by "HFE", "FV", "HC" and "CL" respectively. The present research laid the theoretical foundations to carry out practical researches with a high originality for the Ecuadorian environment. The professional improvement of national specialists and the implementation of prospective actions of consideration are prioritized.